Verschluss des persistierenden Foramen ovale nach ischämischem Schlaganfall - Häusler, Karl Georg; Neugebauer, Hermann (DMW - Deutsche Medizinische Wochenschrift, 2019)
Secondary prevention of otherwise cryptogenic stroke in patients with patent foramen ovale (PFO) has been a matter of debate over nearly three decades. Main issues were that data essentially derived from case-control-studies for a long period and that results from the randomized controlled trials CLOSURE-I, PC Trial and RESPECT, which were published in 2012 and 2013, were interpreted in different ways. The likewise not blinded randomized controlled trials REDUCE, CLOSE and DEFENSE-PFO, which were published in 2017 and 2018, consistently demonstrated superiority of interventional PFO closure compared to secondary stroke prevention with antiplatelet therapy in patients 18 to 60 years with cryptogenic stroke and moderate to severe atrial right-to-left shunt. Consecutively, the German Society of Cardiology, the German Society of Neurology and the German Stroke Society published joint recommendations strongly recommending interventional PFO closure in these patients. This review article briefly summarizes current scientific knowledge. Furthermore, open questions regarding secondary prevention in otherwise cryptogenic stroke patients with PFO are discussed.
Keywords: Schlaganfall; TIA; orale Antikoagulation; Thrombozytenaggregationshemmung; atrialer Shunt